1992
DOI: 10.1213/00000539-199211000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Anesthetic Requirement for Tolerance of Laryngeal Mask Airway and Endotracheal Tube

Abstract: We tested the hypothesis that the laryngeal mask airway (LMA) is tolerated at lighter levels of anesthesia than an endotracheal tube (ET). We studied 20 unpremedicated, nonsmoking ASA physical status I or II patients aged 18-40 yr whose surgery lasted > 1 h. Subjects were randomly assigned to receive either an ET or LMA. Anesthesia was induced with intravenous propofol and the LMA or ET was inserted. The ET-group patients received 1.5 mg/kg of succinylcholine, preceded by vecuronium (0.015 mg/kg IV). Maintenan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
4

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 0 publications
1
37
0
4
Order By: Relevance
“…However, positive pressure ventilation is readily accomplished with the LMA Classic TM [12], the correctly positioned LMA Classic TM will provide some protection against aspiration [13] and the increased risk of aspiration with time is hypothetical, as it has only been the subject of one study [4]. In fact, the LMA Classic TM may offer advantages over the tracheal tube since: (i) spontaneous ventilation is easier due to a reduced work of breathing [14,15]; (ii) positive pressure ventilation can be performed without muscle relaxation due to better tolerance [16]; (iii) the risk of pulmonary infection may be reduced due to non-interference with pulmonary airway resistance [17] and ciliary motility [18]; and (iv) pharyngolaryngeal morbidity may be reduced as the vocal cords are not penetrated and mucosal pressures are lower [19]. A meta-analysis into prolonged use of the LMA Classic TM (based on 16 anecdotal reports, 4 descriptive [20,21] and 7 comparative studies) concluded that there was reasonable evidence supporting its use for 2-4 h, some evidence for 4-8 h, but little evidence for more than 8 h [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, positive pressure ventilation is readily accomplished with the LMA Classic TM [12], the correctly positioned LMA Classic TM will provide some protection against aspiration [13] and the increased risk of aspiration with time is hypothetical, as it has only been the subject of one study [4]. In fact, the LMA Classic TM may offer advantages over the tracheal tube since: (i) spontaneous ventilation is easier due to a reduced work of breathing [14,15]; (ii) positive pressure ventilation can be performed without muscle relaxation due to better tolerance [16]; (iii) the risk of pulmonary infection may be reduced due to non-interference with pulmonary airway resistance [17] and ciliary motility [18]; and (iv) pharyngolaryngeal morbidity may be reduced as the vocal cords are not penetrated and mucosal pressures are lower [19]. A meta-analysis into prolonged use of the LMA Classic TM (based on 16 anecdotal reports, 4 descriptive [20,21] and 7 comparative studies) concluded that there was reasonable evidence supporting its use for 2-4 h, some evidence for 4-8 h, but little evidence for more than 8 h [22].…”
Section: Discussionmentioning
confidence: 99%
“…It is tolerated better at lighter levels of anesthesia. 7 During emergence from anesthesia for nasal surgery, the laryngeal mask maintains an unobstructed airway better than the Guedel airway. 8 It is potentially beneficial therefore to leave it in place until full emergence from anesthesia.…”
Section: Objectif : Le Masque Laryngé (Ml) Est Utilisé En Chirurgie Nmentioning
confidence: 99%
“…tanın (10) 12 (60) 6 (30) 2 (10) 17 (85) 3 (15) (1-3) .. anestezi pratiğinde LM kullanımı, EE ve yüz maskesine ora:rıla daha kolay ve güvenlidir. (1)(2)(3)(4)(5).…”
Section: (100)unclassified